2017
DOI: 10.1007/jhep01(2017)049
|View full text |Cite
|
Sign up to set email alerts
|

Twisted supersymmetry in a deformed Wess-Zumino model in (2 + 1) dimensions

Abstract: Non-anticommutative deformations have been studied in the context of supersymmetry (SUSY) in three and four space-time dimensions, and the general picture is that highly nontrivial to deform supersymmetry in a way that still preserves some of its important properties, both at the formal algebraic level (e.g., preserving the associativity of the deformed theory) as well as at the physical level (e.g., maintaining renormalizability). The Hopf algebra formalism allows the definition of algebraically consistent de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…With the advent of string theory, new interest in noncommutative (NC) space emerged. [6][7][8][9][10][11][12][13][14][15][16][17][18] It has been shown that the dynamics of open strings in the presence of an antisymmetric Bfield can be described in certain limits by a gauge theory on a noncommutative spacetime, 3 namely, one deformed by the Moyal product (whose definition will be given shortly).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of string theory, new interest in noncommutative (NC) space emerged. [6][7][8][9][10][11][12][13][14][15][16][17][18] It has been shown that the dynamics of open strings in the presence of an antisymmetric Bfield can be described in certain limits by a gauge theory on a noncommutative spacetime, 3 namely, one deformed by the Moyal product (whose definition will be given shortly).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of fact, the supersymmetry algebra is highly constrained, and as a consequence supersymmetric models themselves are also very constrained regarding possible terms in the classical Lagrangian and the quantum corrections, which is the main reason that some problematic contributions are avoided in many of the contexts mentioned above. For the same reason, consistent deformations of the supersymmetry algebra are not trivial do obtain, some noteworthy examples involving the use of Hopf algebras [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%